Chemical characteristics, physical and functional properties of some β-bonded polysaccharides: a review - Mohd Nor, Nur ’Ain Najwa; Marikkar, Nazrim; Manaf, Yanty Noorzianna; Mustafa, Shuhaimi (Al-Kindi Center for Research and Development, 2021)
β-bonded polysaccharides are biopolymer substances used as functional ingredients that provide nutritional benefits and health implications. They are extracted from several sources which include higher plants, yeasts, fungi, etc. Applications of β-bonded polysaccharides cover a wide range of benefits, which include new sensorial properties, texture, less use of fat, and improvement to gut health. Incorporation of β-bonded polysaccharides in food formulations is set to grow worldwide and some of them are already used as food ingredients. In this article, we attempted to review recent studies on chemical characteristics, functional properties, and therapeutic values of different β-bonded polysaccharides. Some gaps in knowledge that require further research are also highlighted.